2007
DOI: 10.1128/aac.00414-06
|View full text |Cite
|
Sign up to set email alerts
|

Moxifloxacin, Ofloxacin, Sparfloxacin, and Ciprofloxacin against Mycobacterium tuberculosis : Evaluation of In Vitro and Pharmacodynamic Indices That Best Predict In Vivo Efficacy

Abstract: , and 38 to 100,000 mg/kg (CIP) were performed with a murine aerosol infection model. MXF was the most efficacious agent (3.0 ؎ 0.2 log 10 CFU/lung reduction), followed by SPX (1.4 ؎ 0.1) and OFX (1.5 ؎ 0.1). CIP showed no effect. The ratio of the AUC to the MIC was the pharmacodynamic parameter that best described the in vivo efficacy. In summary, a lack of intracellular killing predicted the lack of in vivo activity of CIP. The in vivo rank order for maximal efficacy of the three active fluoroquinolones was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
161
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(167 citation statements)
references
References 27 publications
6
161
0
Order By: Relevance
“…Moxifloxacin ("Avelox" by Bayer) is a broad-spectrum antibiotic (400 mg/day dose) and is active against both gram positive and gram negative bacteria. It exhibits MIC of 0.5 g/mL against Mtb (Shandil et al, 2007). It displayed early bactericidal activity comparable to INH and rifampin in humans (Pletz 2004;Gosling 2003).…”
Section: Fluoroquinolonesmentioning
confidence: 97%
“…Moxifloxacin ("Avelox" by Bayer) is a broad-spectrum antibiotic (400 mg/day dose) and is active against both gram positive and gram negative bacteria. It exhibits MIC of 0.5 g/mL against Mtb (Shandil et al, 2007). It displayed early bactericidal activity comparable to INH and rifampin in humans (Pletz 2004;Gosling 2003).…”
Section: Fluoroquinolonesmentioning
confidence: 97%
“…Moxifloxacin is metabolized by glucuronidation and sulfation (Phase metabolism) rather than by CYP450-mediated (Phase ) metabolism (Nijland et al, 2007). In vitro studies with moxifloxacin show MICs of 0.25 to 0.5mg/l (Shandil et al, 2007). In vitro studies and studies in mice showed enhanced bactericidal activity of moxifloxacin and isoniazid when coadministered (Yoshimatsu et al, 2002).…”
Section: Moxifloxacin and Gatifloxacinmentioning
confidence: 99%
“…It inhibits bacterial DNA gyrase, an enzyme that is essential for the maintenance of DNA supercoils, which are necessary for chromosomal replication (Shindikar & Viswanathan, 2005). The development of mycobacterial resistance to fluoroquinolones has been described in MDR strains and in strains from HIV-infected TB patients with a low CD4 count (Shandil et al, 2007). Fluoroquinolone resistance is due to stepwise mutations in the quinolone resistancewww.intechopen.com determining region of the mycobacterial gyrA and gyrB genes (Ginsberg, 2008).…”
Section: Moxifloxacin and Gatifloxacinmentioning
confidence: 99%
See 1 more Smart Citation
“…They are be used to study the antibacterial effect of single and combination drug compounds and dosing regimens before in vivo efficacy studies (Bhuda et al, 2009). Bactericidal activity can be determined from a time-kill curve if a greater than 3 log 10 -fold decrease in the number of survivors is noted (Shandil et al, 2007). This is equivalent to 99.9% killing of the inoculums.…”
Section: Time Kill Curvementioning
confidence: 99%